Islam Nusantara: A Semantic and Symbolic Analysis - Mark Woodward (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2017)
This  paper  presents  semantic  and  symbolic  analyzes  of  the  concept  of  Islam Nusantara and how  it  evokes  meaning and  emotion  to  counter  extremist  and violent  transnational  movements,  including  al-Qaeda  and  ISIS,  based  on  the Salafi-Wahhabi  ideology.  The  paper  is  based  on  a  religious,  cultural,  and political  theme  framework  in  two  films  produced  by  Nahdlatul  Ulama  (NU): The Blessing  of  Islam  Nation  (Oceans of  Revelation:  Islam as  a  Blessing  for All Creation) and Launching the Film The Blessing Islam Nusantara. The first is based on elements of Sufism, Javanese and some other Indonesian cultures to  build  a  vision  of  Islam  which  directly  opposes  the  hard  and  non-violent Salafi-  Wahhabi  extremist.  The  latter  promoted  the  film  and  the  potential  of the  Ansor  (NU)  youth  organization  to  combat  extremism  and  terrorism. Theoretically,  I  rely  on  the  insight  by  Goffman's  observations  of  "framing" and "reframing" and Sperber's demonstration that symbolization is one of the cognitive  processes  that  awaken  and  simultaneously  communicate  meaning and emotion.